Successful management of COVID‐19 and associated coagulopathy in a patient with durable left ventricular assist device. Issue 11 (13th August 2020) - Hodges, Kevin; Mubashir, Mujtaba; Insler, Joshua; Estep, Jerry; Hsich, Eileen; Tong, Michael; Insler, Steven; Soltesz, Edward
Abstract: Patients with durable left ventricular assist devices pose special problems for management in the setting of COVID‐19 infection. We describe the successful management of a 44‐year‐old man with severe COVID‐19 infection and HeartMate 3 left ventricular assist device. His course was complicated by cytokine storm and COVID‐19‐associated coagulopathy. We describe our institutional protocol for managing COVID‐19 infection in patients on mechanical circulatory support, focusing on the need for a thoughtful, multidisciplinary approach.